Simple liquid chromatographic method for fluoxetine and its known impurities quantification - GANPISETTI SRINIVASA RAO; K. BASAVAIAH; B. M. RAO; L. KALYANARAMAN; P. SUNIL REDDY; VIJAY KUMAR. R (International Journal of Pharma and Bio Sciences, 2019)
Fluoxetine, an antidepressant medicinal drug, is used to treat reduction of depression, obsessive compulsive disorder. The main objective of the present study is to develop a simple and accurate HPLC method for the quantification of fluoxetine and its impurities in the medicinal tablet as dosage form. Initial method development was carried out based on literate publications and chemical, physical properties of the analytes. Different pH value buffer salts and pH conditions were evaluated and eventually achieved the optimized and rugged chromatographic conditions. Ionic buffer salt octane sufonate and acetonitrile were used for separation. Chromatographic solution A was prepared with 6.5g of octane-1-sufonic acid Sodium salt and 2.9ml of OPA (ortho phosphoric acid) in 1L water and mixed well and sonicated to dissolve, pH of the solution adjusted to 3.0 with diluted 5N NaOH solution. Chromatographic solution B was prepared with solution A and acetonitrile mixture in the ratio of 75:25 v/v. HPLC column Luna phenyl hexyl (250x4.6mm), 5µ column oven temperature 40°C, injection volume 10µL, 1.2ml/min flow rate, 215nm wavelength and each sample analysis time 40min were used. Gradient program is mobile phase-B% ratio at 0min 50%, at 10min 50%, at 15 min 53%, at 30min 53%, at 35 min 50% and at 40min 50%. Method validation was carried out with specificity, linearity, precision, accuracy, ruggedness, limit of detection, limit of quantification and robustness. Validation results confirmed the method stability indicating and application to routine.